Lastare Sebagai Simbol Komunikasi Dalam Budaya Masyarakat Adat Pulau Buru - Sitat Waemese; Untung Suhardi; Anak Agung Ketut Patera (Pasupati, 2022)
This research will discuss about lastare as a communication symbol used by the indigenous people of Buru Island in sending messages. Today the influence of information and communication technology is very massive, this condition has an impact on the traditions of the people who use cultural symbols of their local wisdom as communication symbols, the traditions of the people of Buru Island who use the last symbol as a symbol of communication feel the impact. The main problem in this research is why the lastare message is considered a symbol of communication in the culture of the Buru Island people, and what is the meaning of the lastare message in the communication of the Buru people. The purpose of this research is to use a qualitative descriptive method with data collection through interviews, observation and documentation studies, then the theory used is symbolic interaction. The findings of this study are lastare as a symbol of communication which in the process is an agreement between the tribes on Buru Island, the role of lastare as a symbol that bridges communication between them. Lastare as communication has meaning and understanding based on agreement, then in the communication message there are also other symbols used to interpret the message owned by the communicator.